2017
DOI: 10.1093/annonc/mdx494
|View full text |Cite|
|
Sign up to set email alerts
|

De-escalation strategies in HER2-positive early breast cancer (EBC): final analysis of the WSG-ADAPT HER2+/HR− phase II trial: efficacy, safety, and predictive markers for 12 weeks of neoadjuvant dual blockade with trastuzumab and pertuzumab ± weekly paclitaxel

Abstract: Addition of taxane monotherapy to dual HER2 blockade in a 12-week neoadjuvant setting substantially increases pCR rates in HER2+/HR- EBC compared with dual blockade alone, even within early responders to dual blockade. Early non-response under dual blockade strongly predicts failure to achieve pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 29 publications
5
103
0
2
Order By: Relevance
“…The addition of pertuzumab to a taxane and trastuzumab as first‐line treatment in advanced, HER2‐positive breast cancer improved OS by almost 16 months . The activity of pertuzumab also has been studied in the neoadjuvant setting in several phase 2 trials (Table ) . The NeoSphere trial demonstrated that dual‐blockade with pertuzumab and trastuzumab plus chemotherapy produced a significantly improved pCR rate in the breast compared with chemotherapy and trastuzumab alone (46% vs 29%, respectively).…”
Section: Trastuzumab a Landmark In The Treatment Of Her2‐positive DImentioning
confidence: 99%
See 4 more Smart Citations
“…The addition of pertuzumab to a taxane and trastuzumab as first‐line treatment in advanced, HER2‐positive breast cancer improved OS by almost 16 months . The activity of pertuzumab also has been studied in the neoadjuvant setting in several phase 2 trials (Table ) . The NeoSphere trial demonstrated that dual‐blockade with pertuzumab and trastuzumab plus chemotherapy produced a significantly improved pCR rate in the breast compared with chemotherapy and trastuzumab alone (46% vs 29%, respectively).…”
Section: Trastuzumab a Landmark In The Treatment Of Her2‐positive DImentioning
confidence: 99%
“…Recently, the West‐German Study Group ADAPT trial evaluated the efficacy of 12 weeks of neoadjuvant dual blockade with trastuzumab and pertuzumab with or without weekly paclitaxel in the HER2‐positive/HR‐negative subgroup. That study, with a focus on early responders, demonstrated an impressive pCR rate of 90.5% in the dual blockade plus paclitaxel arm . This pCR rate is the highest ever reported and compares favorably with the rates reported is studies with longer and more aggressive chemotherapy regimens.…”
Section: Trastuzumab a Landmark In The Treatment Of Her2‐positive DImentioning
confidence: 99%
See 3 more Smart Citations